Increasing clinical recruitment rate to a single-site observational study: a quality improvement study - Niamh Ryan; Barry Kevane; Fionnuala Ní Áinle; Hayley Macleod; Nadine Copty; Damien Doherty; Robbie Power; Kate Ahearne; Khalid Saeed; Ellen O’Rourke; Rehman Faryal; Luisa Weiss; et al. (BMJ Open Quality)
Objective Clinical recruitment encompasses a significant challenge in multidisciplinary research, often acting as a bottleneck to timely completion due to slower-than-expected patient enrolment rates. Addressing this, enhanced communication within clinical departments is crucial. A quality improvement (QI) study was initiated in the Mater Misericordiae University Hospital (MMUH) to increase the slow recruitment rate of cancer-associated thrombosis patients to the EXPECT Study.Methods Process and stakeholder mapping as well as Plan Do Study Act (PDSA) cycles highlighted effective initiatives to increase recruitment rates to the study. The PDSA cycle 1 aimed at increasing clinical communication and study education through implementation of work package-1, which included engaging a clinical project sponsor to drive recruitment and increasing study awareness through educational talks/informative materials. The PDSA cycle 2 aimed to increase process efficiency and paired sample acquisition through implementation of work package-2, which included holding weekly QI meetings, building a strong multidisciplinary QI team and mapping the recruitment process. These efforts aimed to increase recruitment from one to four patients enrolled per month, with recruitment progress tracked with a run/bar chart over a 2 year period.Results The communication/education work package-1 initiatives increased the recruitment rate from one to two patients per month, with target enrolment met or exceeded 33% of the QI-project duration. Recruitment numbers nearly doubled in roughly half the timeframe, from 10 patients enrolled in the first 16 months to 18 patients enrolled in the 9 months of the QI study. Furthermore, a greater than threefold statistically significant increase in paired sample acquisition from 20% to 66% was documented following the execution of the second PDSA cycle, aimed at improving process efficiency.Conclusions This QI study highlights the need for a highly engaged study team, specifically the clinical project sponsor driving recruitment from a medical front-line perspective as well as a highly efficient recruitment process.